Double Slit Experiments Showing that Light is Photons Producing both Non-Interference-Pattern and Interference-Pattern in Same Experiment, and thus, Wavefunction Represents Simply Useful Tool Describing Interference-Pattern - Peng, Hui (European Journal of Applied Sciences, 2025)
Recently, Nature magazine made a survey about how Physicists think of what quantum mechanics says about reality. The survey shows that 47% of respondents consider the wavefunction in the quantum mechanics representing simply a useful tool, and 36% respondents consider the wavefunction representing something real. In this article we show that the double slit experiments support the opinion of 47% of respondents. It is the standard understanding that the double slit experiment shows that the light is waves, not particles. The photoelectric experiment shows that the light is particles. The two experiments show the conceptually different natures of the light and thus led to the wave-particle duality of the light. To thoroughly study the real nature of the light in the double slit experiments, we utilizing added Photon-chamber, Shield, Blocker, Lenses, and Metal tubes respectively. We observed the following phenomena in the same double slit experiments: (1) the light is photons before and after passing through the double slit, not waves; and (2) it is the photons that produce both the non-interference patterns in Zone-0, Zong-1 and Zone-2, and the interference patterns in Zone-3 (referred to it as “PhotoWave phenomena”). The observed phenomena show that: (1) the wave-particle duality is invalid; (2) the wavefunction is simply a useful mathematical tool to describe the interference-pattern in Zone-3; (3) the wavefunction cannot be utilized to describe the no-wave phenomena in Zone-0, Zong-1, Zone-2, and Zone-3; (4) support the particle reality of quantum mechanics.